Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T18:56:11+01:00
A) 2x+3y=0.5
3x+y=-1
y=-1-3x
2x+3(-1-3x)=0.5
2x-3-9x=0.5
-7x=3.5/(-7
x=-1/2
y=-1-3*(-1/2)
y=-1+3/2
y=1/2

2x+3y=0.5
3x+y=-1 *(-3)

2x+3y=0.5
-9x-3y=3
dodajemy stronami
-7x=3.5/(-7)
x=-1/2
2*(-1/2) +3y=0.5
-1-0.5=-3y
-1.5=-3y/(-3
y=1/2

b)2x+y=-14
8x+1/2y=35 *(-2
2x+y=-14
-16x-y=-70
-14x=-84 /(-14
x=6
2*6+y=-14
12+y=-14
y=-26


y=-14-2x
8x+1/2(-14-2x)=35
8x-7-x=35
7x=42/7
x=6

y=-14-2*6
y=-14-12
y=-26

c.3x+4y=2//3
5x+7y=1
x=-4/3y+2/3
5(-4/3y+2/3)+7y=1
-20/3y+10/3+7y=1
-6i2/3+7y+3i1/3=1
-1/3y=-2 i1/3//(-1/3
y=7
3x+4*7=2
3x+28=2
3x=-26//3
x=--8i 2/3